2017
DOI: 10.1016/j.jpeds.2016.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity among Young Children with Moderate Acute Malnutrition

Abstract: ObjectiveTo assess the levels of physical activity among young children with moderate acute malnutrition and to identify clinical, biochemical, anthropometric, and sociodemographic correlates of physical activity.Study designIn a cross-sectional study, 1609 children aged 6-23 months wore a triaxial accelerometer (ActiGraph GT3x+; ActiGraph, Pensacola, Florida) for 6 consecutive days, from which total physical activity were determined. Data on morbidity were collected based by history and physical examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…However, since the associations between developmental stage and physical activity were significant even after adjusting for age, they are worth considering in future studies. Similar to the current findings, walkers and crawlers were found to have higher activity (even after controlling for carrying) than not yet mobile infants in the Yameogo et al, study; yet the higher activity we observed in crawlers compared to walkers at certain times of day (7 am, 12 pm, and 7 pm) was not observed in the Yameogo et al, study [ 40 ]. The placement of the accelerometer on the wrist in the present study may have resulted in more movement being detected during crawling when the wrist is involved, than during walking.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, since the associations between developmental stage and physical activity were significant even after adjusting for age, they are worth considering in future studies. Similar to the current findings, walkers and crawlers were found to have higher activity (even after controlling for carrying) than not yet mobile infants in the Yameogo et al, study; yet the higher activity we observed in crawlers compared to walkers at certain times of day (7 am, 12 pm, and 7 pm) was not observed in the Yameogo et al, study [ 40 ]. The placement of the accelerometer on the wrist in the present study may have resulted in more movement being detected during crawling when the wrist is involved, than during walking.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, this is the first study to show sex differences in physical activity intensity and diurnal patterns from such an early age, although these differences are widely reported in older children and adults [ 24 , 35 ]. Various studies conducted internationally have found no differences in objectively measured physical activity between boys and girls at approximately 24-months [ 36 40 ], however it is important to note that none of these studies explored physical activity intensity distributions; and only three explored diurnal patterns of physical activity – one in 19-month toddlers in Australia [ 39 ], one in 6- to 23-month infants/toddlers from Burkino Faso with moderate acute malnutrition [ 40 ], and one in Ethiopian toddlers with severe acute malnutrition in which sex differences were not reported [ 15 ]. The Australian study found that boys were more active than girls in the morning, but observed no overall sex differences [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rehabilitation, compared to 17 days in the present study [15]; although the Ethiopian children were a bit younger and treatment regimes may differ slightly between countries, it is possible that the extra week of hospital treatment in our study may have been incrementally beneficial for restoring natural activity levels. These data in SAM children are complimented by recent observations in children from Burkina Faso with moderate acute malnutrition who accumulated on average 707 cpm of activity (10-s epoch), that is more than twice that of SAM children [24], and further by the even higher levels of physical activity reported in non-wasted toddlers from Malawi (307 counts/15 s 1228 cpm) [25], a level four times as high. These differences in triaxial movement levels are not due to differences in epoch settings, as rerunning analyses in our data with 10-and 14-s epochs before calculating vector magnitude yielded very similar (3-5% lower) estimates; rather, differences are indicative of a positive dose-response relationship between nutritional status and physical activity.…”
Section: Discussionsupporting
confidence: 70%
“…This is plausible, given that the human body undergoes a series of physiological and behavioural changes, including reduction of physical activity, as a response to lowered energy intake (19,20) . In addition to energy deficiency, micronutrient deficiencies, especially Fe deficiency, have been shown to result in reduced activity levels (21)(22)(23)(24) . However, there is limited information on physical activity, measured by modern, objective methods (18,(24)(25)(26) , of young children in resource-poor settings, although some studies from high-income countries exist (27)(28)(29) .…”
mentioning
confidence: 99%